De‐colourization of textile effluent using immobilized Geotrichum candidum: an insight into mycoremediation. (21st December 2020) - Rajhans, G.; Sen, S.K.; Barik, A.; Raut, S.
Abstract: Textile effluent is generally complicated to manage because of its extremely noxious and recalcitrant coloured compositions. Mycoremediation is an extensively used strategy for the competent degradation of hazardous pollutants present in textile effluent. Fungus could be immobilized in synthetic or natural matrices. The current study shows the decolourization of the textile effluent by 85·5 and 98·5% within 6 h using suspended and immobilized fungus, Geotrichum candidum with optimized parameters like inoculum size (5%), pH (4·5), and temperature (30°C). To maintain a high biomass of fungal population and enhance the retention of fungal strain in the contaminated sites, the fungi need to be immobilized. Hence, the fungus was immobilized naturally onto the selected inert support that is, coconut fibres by the means of adsorption, where they grew as active films on the fibres after being grown in the culture broth. The optimized process parameters of inoculum size, fibre quantity and agitation speed for immobilized G. candidum were 5%, 2·2 g l −1 of effluent and 100 rev min −1 respectively. High level of laccase (22 and 25 U l −1 in suspended and immobilized fungal cells treatment respectively) was observed during the process of decolourization and it was found that decolourization was directly proportional to the laccase activity. The UV–vis, FTIR, 1 H NMR and GC‐MS analyses of treated textile industrial wastewater revealed the degradation of toxic pollutants in the textile effluent and formation of lower molecular weight intermediates. The study revealed a higher efficacy of immobilized G. candidum in comparison to suspended fungal culture, employing ligninolytic enzyme laccase, which catalyzes the degradation/transformation of aromatic dyes in the textile effluent thus decolourizing it. Abstract : Significance and Impact of the Study: Using coconut fibres as support matrix, immobilized Geotrichum candidum could enhance the decolourization of textile effluent by 13%. The detection of aromatic amines by UV–vis and FTIR spectral analysis indicated biodegradation of textile effluent by G. candidum, suggesting possible mineralization of textile effluent and formation of new metabolites, due to disappearance of the absorption peaks. The study has provided a natural, economic and effective method for mycoremediation of textile wastewater by the immobilized fungus, G. candidum .